Juridical Analysis of the Cassation Mechanism in acquittal Cases in Indonesia - Zai, Aca Surya Putra (PT. Anagata Sembagi Education, 2024)
Indonesia's criminal justice system, which includes cassation against acquittals, plays an important role in ensuring justice and legal certainty. However, the application of cassation against acquittal has raised debates related to Article 244 of the Criminal Procedure Code, which expressly prohibits the filing of cassation against acquittal. This study aims to analyze the juridical application of the cassation mechanism in the case of an acquittal verdict and its legal implications. The research method used is a normative juridical approach, by analyzing relevant laws and regulations, court decisions, and legal doctrines. The results show that although Article 244 of the Criminal Procedure Code prohibits cassation against acquittals, Supreme Court jurisprudence, such as in the Raden Sonson Natalegawa case, shows flexibility through contra legem interpretation. This has led to complex legal consequences, both positive and negative, which impact on the parties involved and the integrity of the justice system. Therefore, continuous evaluation and adjustment is required to ensure that the goals of justice and legal certainty can be effectively achieved.